Danggui-Shaoyao-San (DSS) Ameliorates Cerebral Ischemia-Reperfusion Injury via Activating SIRT1 Signaling and Inhibiting NADPH Oxidases - Luo, Yunxia; Chen, Hansen; Tsoi, Bun; Wang, Qi; Shen, Jiangang (Frontiers in Pharmacology, 2021)
Danggui-Shayao-San (DSS) is a Traditional Chinese Medicine formula used for treating pain disorders and maintaining neurological health. Recent studies indicate that DSS protects against ischemic brain damage but its underlining mechanisms remain unclear. Herein, we investigated the neuroprotective mechanisms of DSS for treating ischemic stroke in adult male Sprague-Dawley rats with 2 hours of middle cerebral artery occlusion (MCAO) plus 22 hours of reperfusion. Both ethanol extract and aqueous extract of DSS (12 g/kg) were orally administrated to the rats at 30 min before MCAO ischemic onset. We found that (1) ethanol extract of DSS, instead of aqueous extract, reduced infarct sizes and attenuated neurological deficit in the post-ischemic stroke rats; (2) Ethanol extract of DSS down-regulated the expression level of the cleaved-caspase 3 and Bax, and up-regulated the expression of bcl-2, and reduced apoptotic cell death in ischemic brains; (3) Ethanol extract of DSS decreased the production of superoxide and peroxynitrite; (4) Ethanol extract of DSS significantly down-regulated the expression of p67phox but has no effect on p47phox and iNOS statistically. (5) Ethanol extract of DSS significantly up-regulated the expression of SIRT1 in the cortex and striatum of the post-ischemic brains. Importantly, the protective effect of DSS was abolished by EX527, a SIRT1 inhibitor. The results show that DSS could protect cerebral ischemic-reperfusion injury via attenuating oxidative/nitrosative stress and inhibiting neuronal apoptosis in a SIRT1-dependent manner.